Ekplorasi Penyaluran Bantuan Subsidi Upah (BSU) Tenaga Kependidikan Non PNS Selama Pandemi COVID-19 - Amri, Lala Hucadinota Ainul; Amri, Whan Augustin Ainul (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This study aims to explore the distribution of wage subsidy assistance in accordance with the government's objectives, this study will answer whether BSU is right on target and minimizes the spread of the corona virus in the Ministry of Education and Culture. The research method used is exploratory and descriptive. Exploratory is used to provide in-depth explanations, while descriptive is used to analyze the study qualitatively in order to obtain findings and descriptions of a phenomenon that occurs. The results of this study found that; BSU distribution is right on target without any significant obstacles, the distribution mechanism is ineffective in suppressing the spread of the corona virus. Distribution through government banks found technical obstacles in the form of recipient validation which required visiting the channeling bank with a relatively long service time so that it created a potential crowd, even though there had been prevention in the form of strict implementation of protocols but conditions became more complicated where the assistance of teachers and lecturers coincided with government stimulus assistance. other, so the goal of suppressing the spread of the corona virus is contrary to the results of this study. Further research recommends researching appropriate dispensing methods..